2010
DOI: 10.1080/09588220903532971
|View full text |Cite
|
Sign up to set email alerts
|

Supporting collocation learning with a digital library

Abstract: Extensive knowledge of collocations is a key factor that distinguishes learners from fluent native speakers. Such knowledge is difficult to acquire simply because there is so much of it. This paper describes a system that exploits the facilities offered by digital libraries to provide a rich collocation-learning environment. The design is based on three processes that have been identified as leading to lexical acquisition: noticing, retrieval and generation. Collocations are automatically identified in input d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Table 5 lists the top collocations extracted by different measures. Compared to previous study on the English language [24], similar behavior of the three measures was observed. In general, 2 -test and mutual information tend to favor expressions with low frequency and has a repetitive pattern.…”
Section: Stagewise Analysissupporting
confidence: 81%
See 4 more Smart Citations
“…Table 5 lists the top collocations extracted by different measures. Compared to previous study on the English language [24], similar behavior of the three measures was observed. In general, 2 -test and mutual information tend to favor expressions with low frequency and has a repetitive pattern.…”
Section: Stagewise Analysissupporting
confidence: 81%
“…assuming independent events). Such tests include comparing the log-likelihood ratio [12], t-test [13] and 2 -test [8]. Besides, position, span and syntactic rules can also be considered in the association measure [14].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations